El Estado como organismo en la Filosofi?a del Derecho de Hegel. Discusiones en torno al cara?cter metafo?rico o literal del Estado- organismo - Assalone, Eduardo (Revista Eletrônica Estudos Hegelianos, 2018)
In this paper we present a number of interpretations of Hegel’s use of organic representations in the 1821 Grundlinien der Philosophie des Rechts. We back the thesis that for Hegel the State was actually an organism, according with the elements of the Wissenschaft der Logik. Firstly, we expound some prominent positions that construe Hegel’s political organicism literally. Secondly, we summarize the contrary position that claims the metaphorical nature of the State-organism. Finally, we develop the arguments in favor of the Hegelian State as an actual organism. We claim that the State-organism is not for Hegel a natural organism, but a spiritual one.